Dependence of the tooth extraction frequency by orthodontic indications on the type of dentofacial anomalies according to the Engel classification and on the time of the beginning of orthodontic treatment - Makeyev В. Ф.; Chuchmai О. І.; Pylypiv Н. В.; Chuchmai І. Г. (Actual Dentistry, 2020)
Topicality. Orthodontic treatment of patients with anomalies and deformations of dental rows and bite, performed with the removal of certain permanent teeth according to orthodontic indications, still remains a common procedure, despite warnings, especially for the removal of premolars. The aim of study. Determination of the frequency of permanent teeth removal by orthodontic indications depending on the inter-arch relationships according to Engle Class I and Class II in combination with other dentoalveolar deformations. Materials and methods. Clinical examination and orthodontic treatment of 90 people aged 15–27 years, of which 20 males and 70 females. Results. Despite certain warnings regarding the premolars extraction by orthodontic indications, there remain situations when, by clinical and radiological indications, such extraction becomes appropriate and justified in terms of harmonization, aesthetics of the dental bite and facial profile. Conclusions. It was determined that the frequency of premolars extraction by orthodontic indications depends on the severity of the dentofacial pathology and is frequent in pathology of Class II according to Engel classification. The frequency of tooth extraction was higher in patients who sought orthodontic care at a later age.